A context-aware approach for business-to-business collaboration - Tan, Puay Siew (2010)
Businesses operate in value chains to pursue a common goal. Information Technology (IT) is used pervasively to support such complex globalised chains, underlined by Business-to-Business (B2B) collaboration activities. Existing B2B collaborations are often inhibited by costs and long setup time. One of the key challenges is to pervasively connect partners across the entire value chain, with the appropriate service offerings. Thus, it is vital to quickly identify potential partners to form new B2B collaboration or to support formed collaborations with swift decision making abilities. This research proposes a context-aware approach to support such B2B collaboration. Context-awareness relates to the use of situational information (e.g. location of user/company, time and date of expected cargo arrival) for decision-making. The decision could be very computing- centric such as a context-aware database query and search for example. In B2B, the action (or decision) could be when to schedule the next delivery or how to identify suitable partners for collaboration. To realise this context-aware approach, several issues have been addressed: • Understanding and identifying relevant context in B2B collaborations, thereby formulating an appropriate B2B Context Model, • Identifying a relevant context representation and reasoning technique to process the model, and • Developing a method to support decision making, based on a given context of collaboration.